Introducing the Wiley Transplant Peer Review Network. Issue 9 (16th August 2016) - Kirk, A. D.; Malchesky, P. S.; Shapiro, R.; Webber, S. A.; Hirsch, H. H.; Marty, F. M.; Oberbauer, R.; Wekerle, T.; Bühler, L. H.; Labbate, A.; Perry, K.; Wielgus, J.
Abstract : The authors provide an introduction and overview of the Transplant Peer Review Network, a consortium of transplantation journals launched in January 2016.